UPAYA MENINGKATKAN PEMAHAMAN MASYARAKAT DALAM MENCEGAH WABAH COVID-19, DESA BANDUNGREJO KECAMATAN MRANGGEN KABUPATEN DEMAK - Bambang Harjito; Fadhillah Rahmadhani Wahyunintyai (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
The Real Work Lecture (KKN) is an implementation of one of the Tri Darma Higher Education mandates. KKN activities have enormous benefits and goals for the continuity of community life. With the condition of the COVID-19 Pandemic, students of the Sebelas Maret University (UNS) carried out KKN activities by becoming UNS Volunteers Responding to the COVID-19 Outbreak who located in their respective regions. The Community Service Program is implemented  in Pondok Majapahit, Bandungrejo Village, Mranggen District, Demak Regency. As for the problems that occur in the village, not a few people understand about the COVID-19 outbreak, as well as understanding in preventing the spread of the corona virus. Therefore, there is a need for education and outreach about COVID-19 to the public. UNS Volunteer Response Work Program COVID-19 work to achieve the main purpose of increasing the understanding of residents of Pondok Majapahit Area Against Prevention of COVID-19 Plague to break the Chain of Spread of COVID-19. Therefore, in order to support this goal, the activities  are combined under a major theme concerning Supporting Community Understanding of COVID-19. The major  theme, included in the field of social integration,  consists of the following sub-sector program, namely   COVID-19 Transmission Prevention, Proper Handwashing, Social Distancing, Stay at Home Program, Wedang Uwuh Making,